2012
DOI: 10.1073/pnas.1120536109
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric pathways in imidazole glycerol phosphate synthase

Abstract: Protein allosteric pathways are investigated in the imidazole glycerol phosphate synthase heterodimer in an effort to elucidate how the effector (PRFAR,formimino]-5-aminoimidazole-4-carboxamide ribonucleotide) activates glutaminase catalysis at a distance of 25 Å from the glutamine-binding site. We apply solution NMR techniques and community analysis of dynamical networks, based on mutual information of correlated protein motions in the active and inactive enzymes. We find evidence that the allosteric pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

30
427
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(458 citation statements)
references
References 29 publications
30
427
1
Order By: Relevance
“…Allosteric networks were characterized using a community network analysis approach previously applied to investigate allostery in tRNA-protein complexes and other protein systems (24,31,32). This approach constructs a dynamic contact map consisting of a network graph in which each residue is treated as a "node" connected by edges to other nodes when two residues are deemed to be "in contact."…”
Section: Methodsmentioning
confidence: 99%
“…Allosteric networks were characterized using a community network analysis approach previously applied to investigate allostery in tRNA-protein complexes and other protein systems (24,31,32). This approach constructs a dynamic contact map consisting of a network graph in which each residue is treated as a "node" connected by edges to other nodes when two residues are deemed to be "in contact."…”
Section: Methodsmentioning
confidence: 99%
“…Another analysis that involves monitoring the time evolution of residue-residue contact formation and breaking has been proven useful in identifying certain characteristic events during conformational transitions (25). Correlated motions between different biomolecular segments have been identified using cross-correlation analysis and building dynamical networks (25)(26)(27)(28)(29). However, interpretation of the results of such analysis in case of CypA, which exhibit subtle changes upon substrate binding and catalysis, has been ambiguous.…”
mentioning
confidence: 99%
“…Recently, we have advanced these studies and demonstrated that activation of IGPS is dependent on the ability of allosteric effectors to stimulate domainwide motions in the HisF subunit and ligands that induce greater motion within the central (αβ) 8 barrel are more effective activators of glutaminase chemistry (22). NMR and computational community network studies proposed an optimal allosteric pathway through networks of HisF amino acid residues that link the PRFAR binding site and adjacent flexible loop 1 to residues comprising a central hydrophobic cluster essential for catalysis, as well as salt bridge residues at the dimer interface (25,26). These previous results suggest important amino acids in each community that, upon mutation, should disrupt the IGPS allosteric network.…”
mentioning
confidence: 99%
“…(25) In particular, there was an increase in communication between the HisF community, f3′, which contained secondary-structure elements fβ1, fβ2, fβ3, fβ4, fα2, fα2, and hα1, and community h2′, which encompassed the glutaminase active site and hP10 (SI Appendix, Fig. S1).…”
mentioning
confidence: 99%